FOREHAND TOPSPIN STROKE AND BACKHAND STROKE ABILITIES OF TABLE TENNIS ATHLETES AT THE PTM TARUNA CLUB BAJANG MATARAM - Ikwatunnas Ikwatunnas (JOETAL: Journal of Education, Teaching and Learning, 2024)
This research is motivated by the process of evaluating table tennis games in the form of carrying out tests to determine the description of forehand and backhand hitting abilities in table tennis games in Bajang Mataram Cadet PTM Club. The subjects of this research were the PTM Taruna Bajang Mataram Club athletes, totaling 24 athletes. The object of this research is the accuracy of forehand topspin strokes and backhand strokes with a back board test for 30 seconds. The research setting took place in the Bajang Mataram Taruna PTM Club field in academic year 2023/2024. The method used to analyze data is a survey method with skill test and measurement techniques. The results of the research showed that there were two categories of their ability; (1) The forehand ability in table tennis at the PTM Taruna Bajang Mataram Club was in the high category at 23.07%; medium category of 50.00%; and the low category was 26.93%. (2) The ability to hit backhand strokes in table tennis at the Bajang Mataram Taruna PTM Club in the high category was 19.23%; medium category of 57.70%; and the low category was 23.07%. so that’s why, it can be inferred that the ability of forehand topspin and backhand strokes in table tennis at the PTM Taruna Bajang Mataram Club is in the fair/medium category.